(3eONd Edi GdEMUGAs - (3YHO GdbGOQ(B, (3Mdjejs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2004)
(3GdefGgL GdEMUGFjI hHjGfGJgG hJHhjHgG,GdJMdjdGJ GdEMUGFjI,JYOjd GdHjGfGJ hGQJHGWGJgGs
(3HHdjhZQGajG(B:(3U U(B.357-358 (3GdLOGhd(B:(3U U(B.359-375s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s